Solar Panel Light Intensity and Voltage Measurement System Using Atmega328 - Pane, Rangga Rio Pratama; Nengsih, Sri; Morsin, Marlia (PTE FTK UIN Ar-Raniry, 2024)
The need for new renewable energy sources is growing because of several problems, such as high electricity costs, frequent power outages, and dependency on fossil fuels. It's critical to come up with solutions to this problem, like using solar power. Nonetheless, to guarantee a steady supply of energy, solar panels must be well controlled. The primary goal of this study was to create a system that would use an ATmega328 microcontroller, a logger module, and an INA219 voltage sensor, along with a BH1750 light intensity sensor, to detect the voltage and intensity of light on solar panels in real time. The study technique includes the steps of system definition, design, and development using a 4D approach that has been streamlined into 3D. The system's ability to make precise measurements and store data in a readily accessible and processable manner was demonstrated by the test results. Real-time solar panel state monitoring is made possible by the system's primary ATmega328 microprocessor, and data storage in CSV format enables easy analysis. In summary, this system was success for tracking and improving energy efficiency